Unity of Plot: Aristotelian Concept of Plotting in Suresh Triveni’s Jalsa (2022) - Ansar, Muhammad; Saeed, Aqsa (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2024)
Suresh Triveni’s Jalsa: A Film (2022) centers a tragic tale of car accident which predominantly involves two ladies; Maya, a chief journalist and Rukhsana, a cook. The film opens with a hit and run case; Aliya, the daughter of Rukhsana, hit by exhausted Maya and left her in a pool of blood. This incident integrates more characters into the already overstuffed plot; complicit cops, a trainee reporter and a cocky young son of an ambitious politician. Hence, the rarely and never simple plot continues with an intriguing story-line and elements of surprise further. Pertaining to previous, the purpose of this paper is to explore how these distinctive perspectives are convincing to one action and constitute a unified whole. In order to analyze the tightly-executed plot, this paper will utilize the concept of unity-of-plot proposed by Aristotle. In his Poetics (Chapter, VIII), Aristotle defines plot as soul of tragedy and emphasizes on plot as an artistic whole. Moreover, to testify the unity of plot, Aristotle argues that the plot should be grasped by each of its parts without distorting the meaning of the whole. Additionally, the primary intent of this study is to explore how the plot of the chosen film is executed artistically.